Original paperAssociation between -41657C/T single nucleotide polymorphism of DNA repair gene XRCC2 and endometrial cancer risk in Polish women - Michalska, Magdalena M.; Samulak, Dariusz; Bieńkiewicz, Jan; Romanowicz, Hanna; Smolarz, Beata (Polish Journal of Pathology, 2015)
Aim of the study : The XRCC2 gene plays a crucial role in double-strand DNA break repair by homologous recombination. Current literature provides clear evidence that XRCC2 polymorphisms may be associated with the development of certain types of cancer; however, still little is known about their association with endometrial cancer (EC). Material and methods : The single nucleotide polymorphism (SNP) -41657C/T (rs718282) of the XRCC2 gene was investigated by PCR-RFLP in 304 patients with EC and in 200 age- and sex-matched non-cancer controls. Results : The analysis revealed a relationship between XRCC2 -41657C/T polymorphism and the incidence of EC. Endometrial cancer patients showed overrepresentation of the T allele of the SNP. The T/T homozygous variant increased the cancer risk. There were no significant differences between the distribution of XRCC2 -41657C/T genotypes in the subgroups according to histological grade. Conclusions : This is the first study that links the SNP -41657C/T (rs718282) of the XRCC2 gene with EC in Polish women. The results support the hypothesis that this polymorphism may be positively correlated with the incidence of EC.